Microstructure and electrical properties of Li+ ion conducting polymer blend electrolyte films - Rohan Nandeesh Sagar; Ravindrachary Vasachar; Shreedatta Hegde (eXPRESS Polymer Letters, 2023)
Solid polymer electrolytes based on polyvinyl alcohol (PVA)–chitosan (CS) polymer blend and Li–salt doped blend electrolyte films are prepared using the solution cast technique. The Fourier transform infrared spectra showed that the absorption peaks shifted in Li–salt doped polymer blend composites compared to pure blend films: indicating the chemical modifications upon doping. From the UV–visible spectra, the spectral absorption response of Li+ salt–doped polymer blend composites showed a red shift in the absorption band. The optical band gap of the pure polymer blend decreased upon doping. X–ray diffraction studies showed the dopant-dependent structural modification of pure polymer blend upon doping. SEM images also showed the change in the surface morphology of the pure polymer blend upon doping. The termogravimetric analysis study revealed that the thermal stability of the pure polymer blend increases with Li2CO3 concentration. The ionic conductivity of PVA–CS increases with Li–salt concentration, and the maximum conductivity of 7.70·10–5 S·cm–1 is observed for 15 wt% of Li2CO3 salt concentration. The transport property study revealed that the ions are the majority conducting charge carriers in polymer blend composite.